Marijuana use in U.S. teen drivers: a comparison of a road-side survey of reported use and fluid tests for tetrahydrocannabinol (THC) - Joyce C. Pressley; Arushi Arora; Raina Sarmah (BMC, 2019)
Abstract Background Although the growth of state-level legalization of marijuana is aimed at increasing availability for adults and the chronically ill, one fear is that this trend may also increase accessibility in younger populations. The objectives of this study are to evaluate marijuana use in teen driver study participants and to compare their survey self-reported use with oral fluid and blood tests for psychoactive metabolites of tetrahydrocannabinol (THC). Methods The National Roadside Survey (NRS) of 2013-2014 was used to examine marijuana use in drivers aged 16-19 years. Of 11,100 drivers surveyed at 300 U.S. locations in 24 states, 718 were 16-19 years, and 666 (92.8%) provided oral fluid and/or blood. We examined weighted and unweighted data, but present unweighted findings. Kappa statistics, Chi square, and multivariable logistic regressions were used to assess agreement, associations and independent predictors of outcomes. Results More than one-quarter (203/718) of teen drivers reported either using marijuana in the last year or were THC positive. Overall incidence of a THC positive fluid test was 13.7%. In addition to 175 (27.3%) teen drivers who reported use in the last year, 28 (4.4%) who denied using in the past year, tested positive for THC. Of 45 teen drivers reporting use in the last 24 h, more than two-thirds (71.1%) were THC positive. Disagreement between the oral and blood test for 305 teen drivers who had both tests was 17 (5.6%), with a Kappa of 0.78 (95% CI 0.69-0.88). Of THC-positive drivers, nearly 20% started drinking alcohol by age 14 and more than 70% by age 16. Age, gender- and income-adjusted independent predictors of a positive THC test included survey completion during the school year (OR 3.2, 95% CI 1.6-6.2), survey-reported marijuana use in last year (OR 5.3, 95% CI 3.0-9.2), current smoker (OR 2.1, 95% CI 1.1-3.7), and alcohol consumption before age 16 (OR 2.3, 95% CI 1.1-3.7). Conclusions Although specific THC thresholds for safe driving have not been established, taken in the context of teen crash statistics, THC documented impairments and rapidly relaxing marijuana laws, these findings suggest the need for increased vigilance and stepped-up surveillance in teen drivers.